GAYA KEPEMIMPINAN MEMODERASI PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA DOSEN TETAP PERGURUAN TINGGI MARITIM DI KOTA SEMARANG - Cahya Fajar Budi Hartanto, 1352020008 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The objective of this research is to analyze the influence of competence and organizational commitment to the lecturerâs performance on maritime higher education in Semarang moderated by leadership style. Data analysis techniques used are descriptive analysis, instrument quality test, moderated regression analysis by absolute difference, classic assumptions test, model fit test, and hypothesis test. Result of research shows that competence has significant and positive influence to the lecturerâs performance. Meanwhile, organizational commitment and leadership style do not influence the performance. Leadership style also founded does not moderate the influence of competence and organizational commitment to the performance. The equation model of moderated regression generated by this research formulated as Y = 0,532X1 + 0,178X2 â 0,106Z â 0,097|X1-Z| â 0,027|X2-Z|. Data distribution is stated as normal and the model fulfil classic assumptions. Competence, organizational commitment, and leadership style simultaneously influence the performance at 33,8%. Keywords: Performance, Competence, Organizational Commitment, Leadership Style, Moderation